2021
DOI: 10.3168/jds.2020-19789
|View full text |Cite
|
Sign up to set email alerts
|

Genomic predictions for yield traits in US Holsteins with unknown parent groups

Abstract: The objective of this study was to assess the reliability and bias of estimated breeding values (EBV) from traditional BLUP with unknown parent groups (UPG), genomic EBV (GEBV) from single-step genomic BLUP (ssGBLUP) with UPG for the pedigree relationship matrix (A) only (SS_UPG), and GEBV from ssGB-LUP with UPG for both A and the relationship matrix among genotyped animals (A 22 ; SS_UPG2) using 6 large phenotype-pedigree truncated Holstein data sets. The complete data included 80 million records for milk, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…This was already suggested by Lourenco et al (2014). Cesarani et al (2021) showed approximately unbiased evaluations, regardless of data truncation, when the most correct model (an SSGBLUP method) was used. However, for seemingly incorrect models (another SSGB-LUP method or BLUP), Cesarani et al (2021) observed a positive effect (reduction of overdispersion) when truncating old data; the effect was marked in cows and rather small in bulls.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This was already suggested by Lourenco et al (2014). Cesarani et al (2021) showed approximately unbiased evaluations, regardless of data truncation, when the most correct model (an SSGBLUP method) was used. However, for seemingly incorrect models (another SSGB-LUP method or BLUP), Cesarani et al (2021) observed a positive effect (reduction of overdispersion) when truncating old data; the effect was marked in cows and rather small in bulls.…”
Section: Discussionsupporting
confidence: 52%
“…Cesarani et al (2021) showed approximately unbiased evaluations, regardless of data truncation, when the most correct model (an SSGBLUP method) was used. However, for seemingly incorrect models (another SSGB-LUP method or BLUP), Cesarani et al (2021) observed a positive effect (reduction of overdispersion) when truncating old data; the effect was marked in cows and rather small in bulls. The reason why we observed a more marked effect is probably because AI rams did not have as many daughters as AI bulls (hundreds for AI rams compared with thousands or more for AI bulls).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Few researchers have examined AltQP-M. and Masuda et al (2019a) observed a reduction in inflation of GEBV with AltQP-M relative to QP-M for type and production traits in US Holstein. Using more recent data for production traits in the same population, AltQP-M showed greater predictive ability and generally less inflation in GEBV for young bulls and heifers than QP-M (Cesarani et al, 2021). These authors also found the predictive ability of AltQP-M to be more stable than that of QP-M at various pedigree depths.…”
Section: Comparison Among Upg Modelsmentioning
confidence: 84%
“…Despite past limits due to problems with unknown parent groups (UPG) and computational cost, recent studies demonstrated the validity of this method for evaluating breeding values in several different livestock species including dairy (Himmelbauer et al, 2021;Liu and Alkhoder, 2021;Pimentel et al, 2021) and beef cattle (Lourenco et al, 2015), buffalo (Aspilcueta-Borquis et al, 2015;Cesarani et al, 2021a), goats (Teissier et al, 2018), and sheep (Cesarani et al, 2019;Macedo et al, 2020). Recently, better prediction features of ssGBLUP compared with BLUP in US Holstein were reported (Cesarani et al, 2021b). Those authors used about 860k genotyped animals and demonstrated that old phenotypic records (i.e., before 2000) can be removed without reducing prediction accuracy of young selection candidates.…”
Section: Introductionmentioning
confidence: 99%